THE RELATIONSHIP BETWEEN ANXIETY AND HYPEREMESIS GRAVIDARUM IN PREGNANT WOMEN - Syafiuddin, Muthiaturrahmah; Fitriani, Rini; Sakinah, Andi Irhamnia; Nurdin, Azizah; Hakim, Azizul (HEARTY, 2025)
Hyperemesis gravidarum is a psychiatric disorder in pregnant women marked by severe nausea and vomiting, potentially leading to physiological difficulties during pregnancy. Anxiety and other psychological factors might intensify the nausea and vomiting experienced by pregnant women. This study aimed to examine the correlation between anxiety and the incidence of hyperemesis gravidarum in pregnant women at RSIA Ananda Makassar from December 2022 to January 2023. The research methodology utilised was a quantitative study employing a cross-sectional design. The sample comprised 185 pregnant women in the first trimester, diagnosed with hyperemesis gravidarum and those without the condition, selected using purposive sampling. The tools employed included a demographic questionnaire and the Perinatal Anxiety Screening Scale (PASS), analysed via the Chi-Square test. The study’s results produced a p-value of 0.000, signifying a correlation between the two variables, hence affirming the alternative hypothesis. This study concludes that a significant correlation exists between anxiety levels and the incidence of hyperemesis gravidarum in pregnant women at RSIA Ananda Makassar in 2023, highlighting the need for educational initiatives for pregnant women about the detrimental effects of anxiety on hyperemesis gravidarum.